2007
DOI: 10.1074/jbc.m701827200
|View full text |Cite
|
Sign up to set email alerts
|

Control and Regulation of KplE1 Prophage Site-specific Recombination

Abstract: KplE1 is one of the 10 prophage regions of Escherichia coli K12, located at 2464 kb on the chromosome. KplE1 is defective for lysis, but it is fully competent for excisive recombination. In this study, we have mapped the binding sites of the recombination proteins, namely IntS, TorI, and IHF on attL and attR, and the organization of these sites suggests that the intasome is architecturally different from the canonical form. We also measured the relative contribution of these proteins to both excisive and integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 49 publications
4
38
0
Order By: Relevance
“…None of the 35 identified ORFs yielded any similarity to previously described excisionases. However, when the vpiT (VC0817) amino acid sequence was submitted to HHpred, 52 amino acids near the N terminus displayed a distant relationship to TorI, a previously characterized excisionase (25,31,52). Although the shared identity in this region was 12%, with an E value of 0.0061, the predicted secondary elements of these regions were nearly identical (see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the 35 identified ORFs yielded any similarity to previously described excisionases. However, when the vpiT (VC0817) amino acid sequence was submitted to HHpred, 52 amino acids near the N terminus displayed a distant relationship to TorI, a previously characterized excisionase (25,31,52). Although the shared identity in this region was 12%, with an E value of 0.0061, the predicted secondary elements of these regions were nearly identical (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In TR integrase-encoding prophages, it was demonstrated that the excision event also requires an additional protein, an excisionase or recombination directionality factor (RDF) (24)(25)(26)(27)(28). In fact, it is believed that all TR integrases require an RDF to perform excision (20,29).…”
mentioning
confidence: 99%
“…Examination of the deposited genome of E. coli DH10b (the parent of Top10) (GenBank TM accession number NC_010473.1) revealed a three-ORF cluster with high sequence identity to S. flexneri bacteriophage (gtr) glucosylation clusters, belonging to the prophage KplE1 (19). The -red recombination system was used to remove the first gene in this cluster, a gtrA homologue annotated yfdG, which overlaps with the first four nucleotides of the gtrB homologue, yfdH.…”
Section: Differential Reactivities Of Native R Terrigena Lps and Lpsmentioning
confidence: 99%
“…The association of glucosylation modification with the Wzy-dependent pathway may reflect the limits to which systems have been characterized at a bioinformatics and biochemical level or may result from the glycosylation system being critically dependent on elements of the Wzy-dependent machinery. Here, we examine the possibility that the ABC transporter-dependent pathway provides an intrinsic mechanistic barrier for the glucosylation process by examining the potential for the native E. coli K-12 glucosylation machinery encoded by prophage KplE1 (19) to modify target residues supplied by a heterologous ABC transporter-dependent O-antigen from Raoultella terrigena ATCC 33257 (see Fig. 2).…”
mentioning
confidence: 99%
“…KplE1 (also named CPS-53) is highly defective (it has only a 10-kb genome). However, it is fully competent for site-specific recombination and provides fitness to its host under oxidative stress conditions (28)(29)(30). HK620 is a fully infectious P22-like phage that shares a highly conserved site-specific recombination module with KplE1 (27,28).…”
mentioning
confidence: 99%